Unlocking the potential of green infrastructure in residential areas: a comprehensive systematic review - Md Sahak, Nursah'aidah; Mohd Yunos, Mohd Yazid; Maulan, Suhardi; Ismail, Nor Atiah (Human Resources Management Academic Research Society (HRMARS), 2025)
Green infrastructure (GI) offers a sustainable solution to urban challenges in residential areas, providing benefits like effective stormwater management, climate mitigation, and improved well-being. This review follows PRISMA guidelines to analyse global case studies and research on GI, evaluating its potential, challenges, and opportunities in residential settings. Data were gathered from peer-reviewed articles and grey literature, focusing on ecosystem services, sustainability, and urban resilience. The review highlights GI's multifunctionality, showing benefits such as flood risk reduction, biodiversity enhancement, and urban cooling, while addressing implementation challenges. Global case studies, including Sponge City programs in China, SuDS in Newcastle, and vertical gardens in Singapore, illustrate diverse GI applications. A comprehensive approach involving public awareness, policy support, technical training, financial incentives, and stakeholder collaboration is key to overcoming barriers. In Malaysia, adopting frameworks like SuDS and eco-friendly solutions, such as rain gardens and green roofs, can enhance urban stormwater management and resilience. This study emphasizes equitable GI adoption, addressing environmental inequality, and fostering community engagement. Future research should assess GI benefits, understand demographic variations, and integrate GI with urban systems through cross-disciplinary collaboration. By bridging knowledge gaps and fostering partnerships, GI can create sustainable, resilient residential communities, supporting environmental conservation and quality of life for residents.